PENGARUH PELATIHAN, MOTIVASI KERJA, PROFESIONALISME, DAN KOMITMEN ORGANISASI PADA KINERJA ACCOUNT REPRESENTATIVE (Studi di Kantor Pelayanan Pajak Madya Denpasar dan Pratama Denpasar Timur) - Ni Made Indri Desiyanti; I Wayan Suka Negara; Ni Wayan Yuniasih (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2019)
Tax is one source of the State Budget (APBN). Tax service quality is determined by the performance of tax employees, one of which is the performance of Account Representative (AR). With the help of an Account Representative (AR), taxpayers will be easier to administer taxation. Account Representative (AR) is a professional staff whose duty is to provide information and assist taxpayers in completing their tax obligations (Ananta, 2010). The dependent variable used in this study is the performance of Account Representative (AR) and its independent variables are training, work motivation, professionalism, and organizational commitment. The population in this study was all employees of the Account Representative (AR) in the Tax Office (KPP) Middle and East Denpasar as many as 46 people employees of Account Representative (AR). Data collection is done by distributing questionnaires. Data analysis in this study used Multiple Linear Regressions Method. The results of the research and hypothesis testing that have been done can be concluded that work motivation has a positive effect on the performance of Account Representative (AR). Training, professionalism, and organizational commitment have no effect on the performance of Account Representatives (AR). This may be due to the relatively fast transfer of employees so that training and the level of professionalism of employees are not optimal. They need time to make adjustments and learn the characteristics of the taxpayer being handled.